A Novel Idiopathic Atrial Calcification: Pathologic Manifestations and Potential Mechanism - Li, Bowen; Liu, Qingbo; Chen, Xihui; Chen, Tangdong; Dang, Wenhui; Zhao, Jing; Cui, Guangbin; Chen, Kun; Wu, Yuanming (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac calcification is a type of ectopic pathologic calcification of unknown etiology and mechanisms. Once diagnosed, the location, extent and morphology of the calcified lesions, as well as their functional significance in the heart, are usually the focus of case reports. Calcification is mostly distributed in myocardium, but rarely reported in atrium. In addition, because of limited sampling and complex pathological mechanisms, the etiology underlying the formation of these calcified lesions also remains unclear. Methods Two cardiac calcifications were found in a patient, died of trauma-induced subarachnoid hemorrhage after slightly drinking, during a standard autopsy. The location and morphological characteristics of the calcified lesions were determined by computed tomography (CT) and CT-based 3D reconstruction. The specific histopathological characteristics of the lesions were determined by multi-staining. The concentration of free calcium and inorganic pyrophosphate (PPi) in plasma reflected the change of calcium metabolism. The expression and membranal localization of the ATP Binding Cassette Subfamily C Member 6 (ABCC6) in hepatocytes were detected by immunofluorescence. The variants of the ABCC6 were detected by Sanger sequencing and potential pathogenic variants were further identified by in silico analysis. Results The present study describes a patient with idiopathic calcification with two pear-shaped and irregularly hollow lesions symmetrically distributed in the patient's atrium. Massive accumulation of calcium salts was identified by multi-staining. For this patient, the plasma concentration of free calcium was higher than the control, indicating that calcium metabolism was disturbed. Furthermore, the plasma PPi of the patient was lower than the normal. By using immunofluorescence, the expression and membranal localization of ABCC6 was decreased and impaired in hepatocytes, respectively. Combined with Sanger sequencing and in silico analysis, 7 variants were identified. Conclusions This study described a novel patient with symmetrically distributed idiopathic atrial calcifications. Furthermore, all the results indicated that these pathologic calcifications may be secondary to reduced plasma PPi content due to ABCC6 dysfunction in hepatocytes. Moreover, these findings provided novel clues to the pathogenesis, clinical diagnosis and treatment of idiopathic atrial calcification in future.